Ste12/Fab1 phosphatidylinositol-3-phosphate 5-kinase is required for nitrogen-regulated mitotic commitment and cell size control. - David Cobley; Lenka Hálová; Marie Schauries; Adrian Kaczmarek; Mirita Franz-Wachtel; Wei Du; Karsten Krug; Boris Maček; Janni Petersen (PLoS ONE)
Tight coupling of cell growth and cell cycle progression enable cells to adjust their rate of division, and therefore size, to the demands of proliferation in varying nutritional environments. Nutrient stress promotes inhibition of Target Of Rapamycin Complex 1 (TORC1) activity. In fission yeast, reduced TORC1 activity advances mitotic onset and switches growth to a sustained proliferation at reduced cell size. A screen for mutants, that failed to advance mitosis upon nitrogen stress, identified a mutant in the PIKFYVE 1-phosphatidylinositol-3-phosphate 5-kinase fission yeast homolog Ste12. Ste12PIKFYVE deficient mutants were unable to advance the cell cycle to reduce cell size after a nitrogen downshift to poor nitrogen (proline) growth conditions. While it is well established that PI(3,5)P2 signalling is required for autophagy and that Ste12PIKFYVE mutants have enlarged vacuoles (yeast lysosomes), neither a block to autophagy or mutants that independently have enlarged vacuoles had any impact upon nitrogen control of mitotic commitment. The addition of rapamycin to Ste12PIKFYVE deficient mutants reduced cell size at division to suggest that Ste12PIKFYVE possibly functions upstream of TORC1. ste12 mutants display increased Torin1 (TOR inhibitor) sensitivity. However, no major impact on TORC1 or TORC2 activity was observed in the ste12 deficient mutants. In summary, Ste12PIKFYVE is required for nitrogen-stress mediated advancement of mitosis to reduce cell size at division.